Multiple sulfur isotopic composition of main group pallasites support genetic links to IIIAB iron meteorites. (1st March 2018) - Dottin, James W.; Farquhar, James; Labidi, Jabrane
Abstract: This study reports the quadruple sulfur isotope composition of troilite nodules from Main Group Pallasites. Values range from −0.23‰ to 0.34‰ (average = 0.03 ± 0.17‰ S.D.) in δ 34 S and 0.008‰ to 0.025‰ (average = 0.018 ± 0.006‰ S.D.) in Δ 33 S and −0.38 to −0.01 (average = −0.17 ± 0.11‰ S.D.) in Δ 36 S. The variance of these analyses is comparable to estimates of analytical uncertainty (±0.3‰, ±0.008‰, and ±0.3‰, for δ 34 S, Δ 33 S, and Δ 36 S, respectively) and the average of these values is taken as a constraint on the composition of sulfur in the MG Pallasite parent body. The different Δ 33 S value compared to CDT and IAB iron meteorites at a similar δ 34 S value is interpreted as a mass-independent signature. This signature is similar in magnitude and direction to previously published values observed in IIIAB iron meteorites, further supporting a genetic relationship between the two groups of meteorites.